INTERPRETATION OF THE œSEGALARIAK SONG BY JOSU ELBERDIN BY YOSAFAT RANNU LEPONG IN THE REVIEW OF CONDUCTING TECHNIQUE - hafi hilmiah almanda (Repertoar, 2020)
A conductor in presenting music requires a concept or technique of how the music to be displayed becomes more beauthiful and lively. This research to describe the method and application of the technique of conducting the song "Segalariak" by Yosafat. This research uses a qualitative method. Techniques collection data are done by observation, interview and documentation. The method of interpretation used by Yosafat when interpreting the song "Segalariak" was the first to understand the form of songs, harmony, rhythm and time, tempo, song lyrics and dynamics. The interpretation in the conducting technique which is done by Yosafat on the song "Segalariak" the first stage the technique of attack carried out when the song will begin and the tempo, time and dynamics change. The two stages when singing is done when meeting dynamics. The last stage of ending the song (realese) is done when ending the song.